Dampak Pembangunan Jalan di Guguak Malalo terhadap Aksesibilitas, Pariwisata, dan Kesejahteraan Masyarakat - Esy Maestro; Alya Miftahul Adha; Racma Dina; Rian Septiawan; Savia Anggi Mustikasari; Yola Ananda Musma (Jurnal Pengabdian Kepada Masyarakat, 2025)
This study aims to analyze the impact of road development in Nagari Guguak Malalo, Batipuh Selatan District, Tanah Datar Regency, West Sumatra on three main aspects: accessibility, tourism, and community welfare. This nagari, located on the edge of Singkarak Lake, has nature and culture-based tourism potential but was previously constrained by narrow, steep road access with landslide risks. The research employed a qualitative method with a case study approach through semi-structured interviews and observations. Results show that road development provides significant positive impacts on accessibility by reducing travel time and enabling four-wheeled vehicles to access the area. From a tourism perspective, the new infrastructure facilitates community-based tourism development such as the "Pesona Guguak Malalo" event, although still constrained by financial support. In the agricultural sector, road development improves the efficiency of agricultural product distribution and reduces the risk of product damage during transportation. However, the study also identifies challenges such as suboptimal construction quality and the need for community human resource development. The research conclusion emphasizes that infrastructure development must be accompanied by community empowerment programs to ensure sustainable benefits.